INDONESIA’S ENVIRONMENTAL DIPLOMACY UNDER THE JOKO WIDODO ADMINISTRATION (2014–2024): A CRITICAL CONSTRUCTIVIST PERSPECTIVE - Verdinand Robertua; Ruth Margaretha (Sociae Polites, 2026)
In the past decade, environmental diplomacy has become one of the key agendas in international relations as threats from climate change and ecosystem degradation intensify. Amid these developments, Indonesia under the presidency of Joko Widodo has demonstrated active engagement through various global commitments, ranging from the ratification of international agreements to participation in climate change forums. However, this role raises questions about the extent to which Indonesia’s environmental diplomacy reflects substantive commitment or merely representational efforts to project an image of a country responsive to global issues. This paper discusses how environmental norms are represented in Indonesia’s diplomatic practices and how such representations are used to shape the country’s position and legitimacy at the international level. Through an analysis of official statements and patterns of diplomatic engagement, the article shows that there is a disconnect between international narratives and domestic implementation, suggesting that environmental diplomacy functions more as a means of identity-building rather than as a driver of structural change. The paper concludes that greater consistency between diplomacy and environmental policy is needed so that Indonesia’s role in global issues becomes not only symbolic but also produces tangible outcomes. Keywords: Environmental Diplomacy, Indonesia, Norm Representation, Global Environmental Governance, One decade of Joko Widodo's administration